The two-phase closed tubular cryogenic thermosyphon. (January 2015) - Bolozdynya, A.I.; Dmitrenko, V.V.; Efremenko, Yu.V.; Khromov, A.V.; Shafigullin, R.R.; Shakirov, A.V.; Sosnovtsev, V.V.; Tolstukhin, I.A.; Uteshev, Z.M.; Vlasik, K.F.
Abstract: The heat transfer characteristics of a two-phase closed tubular cryogenic thermosyphon filled with nitrogen fluid have been investigated. The thermosyphon consists of a 1.1 cm inside diameter, 5 m long copper tube coated with a few layers of the high-vacuum superinsulation and enclosed into a vacuum jacket. A free-boiling liquid nitrogen pool has been used as a cooling machine. The system is compact, free from mechanical vibrations, and can provide thermal stabilization of remotely located devices in the temperature range of 80–120 K with the heat transfer limit up to 100 W.